x+1分之1+x-1分之1+x平方-2x+1分之1
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/06 21:53:42
x+1分之1+x-1分之1+x平方-2x+1分之1x+1分之1+x-1分之1+x平方-2x+1分之1x+1分之1+x-1分之1+x平方-2x+1分之11/(x+1)+1/(x-1)+1/(x²
x+1分之1+x-1分之1+x平方-2x+1分之1
x+1分之1+x-1分之1+x平方-2x+1分之1
x+1分之1+x-1分之1+x平方-2x+1分之1
1/(x+1)+1/(x-1)+1/(x²-2x+1)
=1/(x+1)+1/(x-1)+1/(x-1)²
=[(x-1)²+(x-1)(x+1)+(x+1)]/[(x+1)(x-1)²]
=(x²-2x+1+x²-1+x+1)/[(x+1)(x-1)²]
=(2x²-x+1)/[(x+1)(x-1)²]
(x平方-2x分之x+2-x平方-4x+4分之x-1)乘4-x分之x
X平方+x分之x-1除以x平方分之x平方-2x+1-x分之1
x分之2-x的平方分之2x-1
x的平方-4分之x-x+2分之1
1-x平方-4分之4x=x+2分之x+x-2分之2
x的平方-9分之2x+3-x分之1+x+3分之x+2
(x-2分之3x-x+2分之1)乘x分之x平方-4
x²+x分之2+x²-x分之3=x平方-1分之4
x平方+x分之7 + 1-x平方分之6=x-x平方分之1
1.【x-1分之x平方+3x+2】+【6分之2+x-x平方】-【10-x分之4-x平方】2.【x+1-1分之1-x】除以【x-x平方分之x-1】3.【x平方-4分之x平方-x-6】+【x+2分之x-3】这个结果再除以【x+1分之x-3】4.【x分之x-y】乘以
x的平方-x-2分之x的平方-1除以2x-4分之x
4-4x分之9x-9 化简 x平方+x-2分之x平方-1
化简x平方+x-2分之x平方-1
先化简,再求值:(x-3分之2x-x+3分之x)乘x分之x平方-9,其中x=1;x平方+x分之1+x平方-x分之2=x平方-1分之2,解方程
x平方-x+1=x平方-x分之6
x-3分之x-x的平方-3x分之x+6+x分之1
x平方-9分之2加x(x-3)分之x-2=x平方+3x分之1急.
计算 【(x+1)分之(x-1)-(x+2)分之(x+1)】/(x的平方+4x+4)分之(x+3)